2018
DOI: 10.1097/gco.0000000000000475
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic myomectomy: a comparison of techniques and review of current evidence in the management of abnormal uterine bleeding

Abstract: The evidence suggests that no one technique should be used for all patients, but rather a choice of technique should be taken on a case-by-case basis, depending on the myoma number, size, type, and location. Gynecologists must become knowledgeable about each of these techniques and their associated risks to safely offer these surgeries to their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
2
17
0
2
Order By: Relevance
“…Myomectomy was done in more than two-thirds of those who received surgical management due to the fact that fibroids was the most common structural cause of bleeding; its fertility sparing benefit and popularity among the study participants who were women of reproductive age. This finding corroborates with that reported in a systematic review [19] which reported that among women with myomas at risk of abnormal uterine bleeding; myomectomy is a gold-standard treatment option for those women who wish to preserve their fertility. This is coupled by its safety, minimal invasiveness and greater patient satisfaction [19,20] as corroborated in the current study's findings.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Myomectomy was done in more than two-thirds of those who received surgical management due to the fact that fibroids was the most common structural cause of bleeding; its fertility sparing benefit and popularity among the study participants who were women of reproductive age. This finding corroborates with that reported in a systematic review [19] which reported that among women with myomas at risk of abnormal uterine bleeding; myomectomy is a gold-standard treatment option for those women who wish to preserve their fertility. This is coupled by its safety, minimal invasiveness and greater patient satisfaction [19,20] as corroborated in the current study's findings.…”
Section: Plos Onesupporting
confidence: 91%
“…This finding corroborates with that reported in a systematic review [19] which reported that among women with myomas at risk of abnormal uterine bleeding; myomectomy is a gold-standard treatment option for those women who wish to preserve their fertility. This is coupled by its safety, minimal invasiveness and greater patient satisfaction [19,20] as corroborated in the current study's findings.…”
Section: Plos Onesupporting
confidence: 91%
“…Many strategies or principles for decreasing the risk of developing IUA, such as the reduced use of electrosurgery and the minimization of trauma to the healthy endometrium and myometrium, have been proposed [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Additionally, many biomaterial agents, barrier methods, and cell or bio-agent therapies have been applied [ 14 , 16 , 24 , 27 , 28 , 29 , 30 , 31 , 35 , 37 , 40 , 43 , 44 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Figure 3 shows the recent development of agents available for the primary prevention of IUA after uterine surgery.…”
Section: Primary Prevention Of Intrauterine Adhesion (Iua)mentioning
confidence: 99%
“…First, the impact of surgical technology on the development of IUA should be considered, although it is unknown whether one technique is better than another [ 2 ], partly because of the presence of many confounding uncontrolled variables, meaning the data were derived with difficulty [ 73 ]. The most frequently discussed areas of surgical technology fit into five categories: (1) types of intrauterine instrumentation, (2) types of energy (bipolar or unipolar systems), (3) types of distending media (normal saline, dextran water or glycine), (4) types of intrauterine pressure (low pressure versus high pressure), and (5) preoperative additional therapy or postoperative additional therapy.…”
Section: Primary Prevention Of Intrauterine Adhesion (Iua)mentioning
confidence: 99%
“…Containment systems like endoscopic bags are now available for both electrical and manual morcellation 17. For sub-mucous fibroids, hysteroscopic myomectomy is the treatment of choice to improve bleeding and to normalize the uterine cavity 18. In selective cases of UFs associated to metrorrhagia, in women who do not wish to preserve fertility, a treatment option could be also hysteroscopic endometrial ablation 12,13.…”
Section: Introductionmentioning
confidence: 99%